Analysis of the Distribution and Temporal Trends of Grade and Stage in Urothelial Bladder Cancer in Northern New England from 1994 to 2004. (12th April 2012) - Schned, Alan R.; Lenz, Petra; Moore, Lee E.; Johnson, Alison; Jones, Michael; Kida, Masatoshi; Silverman, Debra T.; Schwenn, Molly; Kelsey, Karl T.; Andrew, Angeline S.; Baris, Dalsu; Karagas, Margaret R.
Abstract : We investigate the distribution of bladder tumor category and stage in Northern New England by geographic region, smoking status, and over time. 1091 incident bladder cancer cases from the New England Bladder Cancer Study (NEBCS), a large population-based case-control study carried out in Maine, New Hampshire, and Vermont (2001–2004) and 680 bladder cancer cases from previous case-control studies in New Hampshire (1994–2000) were used in the analysis. Of 1091 incident bladder cancer cases from the NEBCS, 26.7% of tumors were papillary urothelial neoplasms of low malignant potential (PUNLMP), 26.8% low-grade papillary urothelial carcinomas (PUC-LG), 31.3% high-grade papillary urothelial carcinomas (PUC-HG), 9.1% nonpapillary urothelial carcinomas (non-PUC), and 4.3% carcinoma in situ (CIS). Approximately 70% of cases were noninvasive (Tis/Ta), and all PUNLMP cases were of the Ta category. By contrast, half of all PUC-HG carcinomas were invasive. Short-term time trend analysis within the NEBCS (2001–2004) indicated an increase in the percentage of PUNLMP (P -trend <0.0001) paralleled by a decrease in PUC-LG (P -trend = 0.02) and for PUC-LG an increase in the percentage of non-invasive tumors (P -trend 0.04). Our findings suggest possible short-term trends with an increase in the percentage of PUNLMP and a change in the percentage of PUC-LG towards non-invasive disease.